Pure Phase Co3O4 Anchored on Nitrogen-Doped Porous Carbon for High-Performance Lithium-ion Batteries - Ruan, Qingling; Yang, Zhehan; Liu, Yan; Xu, Junjie; Zhang, Jie; Dai, Jinhang; Gu, Xingxing (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
Transition metal oxides (TMOs), due to their high theoretical capacity, and long cycling stability, have received increasing attention as the anode materials for lithium-ion batteries (LIBs). In this work, a kind of TMOs, Co3O4, anchored on nitrogen-doped porous carbon (NC), has been successfully synthesized via calcining cobalt salts and biomass precursor together. The synthesized Co3O4/NC as an anode material for lithium-ion batteries illustrates excellent cycling performances. At a current density of 1.0 A.g-1, the Co3O4/NC anode could maintain a superior high reversible capacity of 1131.4 mAh.g-1 after 2000 cycles. Even if the current increases to 8.0 A.g-1, it still shows a reversible capacity of 502.9 mAh.g-1. Such excellent electrochemical performances could be attributed to the high specific surface area of NC that facilitates the uniform dispersion of Co3O4 nanoparticles on it as well as the abundant porous structure and good conductivity of NC that enhance the Li+ transfer and electrons transfer, respectively. In a word, this work provides a simple strategy for synthesizing the NC-supported pure phase Co3O4 composite anode material for realizing high-performance LIBs. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).